Chemical Characteristics of Precipitation in a Typical Urban Site of the Hinterland in Three Gorges Reservoir, China. (19th March 2018) - Zhang, Liuyi; Qiao, Baoqing; Wang, Huanbo; Tian, Mi; Cui, Jian; Fu, Chuan; Huang, Yimin; Yang, Fumo
Abstract : Major water-soluble ions were analyzed for two-year precipitation samples in Wanzhou, a typical urban site of the hinterland of Chinese Three Gorges Reservoir. The pH values of the precipitation were in the range of 4.0 to 8.3, and the volume-weighted mean (VWM) value was 5.0. The concentration order of anions and cations was as follows:SO 4 2 - > NO 3 - > Cl - > F - andNH 4 + > Ca 2 + > Na + > K + > Mg 2 +, respectively. Good correlations were found betweenSO 4 2 - andNH 4 +, SO 4 2 - and Ca 2+, NO 3 - andNH 4 +, andNO 3 - and Ca 2+, implying their co-occurrence in the precipitation, most likely as (NH4 )2 SO4, (NH4 )HSO4, NH4 NO3, CaSO4, and Ca(NO3 )2 . The sum of all measured ions was 416.4 μ eq L −1, indicating serious air pollution in Wanzhou.NH 4 + and Ca 2+ were the most important ions neutralizing the acidic compounds in the precipitation; their major sources included agricultural activity and crustal dust. Local anthropogenic activities, for example, coal burning and traffic related sources, contributed most ofSO 4 2 - andNO 3 - . The equivalent concentration ratio ofSO 4 2 - / NO 3 - was 4.5, indicating that excessive emission of sulfur was the main reason leading to the precipitation acidity in Wanzhou. However, this ratio was lower than the ratio (5.9) in 2000s in Wanzhou, indicating that the contribution of nitric acid to the acidity of precipitation was strengthening.